Kepincangan perumahan Malaysia : adat dan ritual kaum Cina - Mohamad Tajuddin Haji Mohamad Rasdi, 1962-; Cheah, Ding Ding, 1984- (Johor Bahru, Johor Darul Ta'zim, Malaysia : Penerbit UTM Press, Universiti Teknologi Malaysia, 2011)
Chinese dwelling and domestic settings related to its culture in Malaysia.
Includes bibliographical references (page [99]-100) and index
Keywords: Architecture, Domestic -- Malaysia; Chinese -- Dwellings -- Malaysia; Chinese -- Malaysia -- Civilization; Chinese -- Malaysia -- Social life and customs; Vernacular architecture -- Malaysia